PENGARUH STRATEGI PELATIHAN DAN PENGETAHUAN KONSEP DASAR EKOLOGI TERHADAP SIKAP TENAGA KERJA YANG BERWAWASAN LINGKUNGAN - J. E. Endang D. P (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2011)
This study aimed at investigating the effect of training strategies and knowledge of basic concepts of ecology on environmental-based attitude of prospective labors. The experimental study with 2x2 factorial designs was conducted at the Regional Labor Training Centre of West Jakarta with training participants of the center involved as subjects of the study. The study has been focused on four Research Questions: (1) Is there any significant difference in the environmental-based attitude of prospective labors who were trained with fieldtrip strategy and those who were trained with group discussion strategy?; (2) Is there any significant difference in the environmental-based attitude of prospective labors with high level of knowledge of basic concepts of ecology who were trained with fieldtrip strategy and those who were trained with group discussion strategy?; (3) Is there any in the environmental-based attitude of prospective labors with low level of knowledge of basic concepts of ecology who were trained with fieldtrip strategy and those who were trained with group discussion strategy?; and (4) Is there any interactions between the effect of training strategies and knowledge of basic concepts of ecology on the environmental-based attitude of prospective labors?Findings of the study signify that (1) there is no significant difference in the environmental-based attitude of prospective labors who were trained with fieldtrip strategy and those who were trained with group discussion strategy; (2) prospective labors with high level of knowledge of basic concepts of ecology who were trained with fieldtrip strategy show better environmental-based attitude compared to those who were trained with group discussion strategy; (3) prospective labors with low level of knowledge of basic concepts of ecology who were trained with group discussion strategy show better environmental-based attitude compared to those who were trained with fieldtrip strategy; and (4) there is an interaction between training strategies and knowledge of basic concepts of ecology on the environmental-based attitude of prospective labors.To sum up, to promote better environmental-based attitude of prospective labors requires appropriate training strategies that is determined by carefully considering their knowledge level on basic concepts of ecology.